GSH and H2O2 Co‐Activatable Mitochondria‐Targeted Photodynamic Therapy under Normoxia and Hypoxia. Issue 29 (20th May 2020) - Sun, Jian; Du, Ke; Diao, Jiajie; Cai, Xuetong; Feng, Fude; Wang, Shu
Abstract: Currently, photosensitizers (PSs) that are microenvironment responsive and hypoxia active are scarcely available and urgently desired for antitumor photodynamic therapy (PDT). Presented herein is the design of a redox stimuli activatable metal‐free photosensitizer (aPS), also functioning as a pre‐photosensitizer as it is converted to a PS by the mutual presence of glutathione (GSH) and hydrogen peroxide (H2 O2 ) with high specificity on a basis of domino reactions on the benzothiadiazole ring. Superior to traditional PSs, the activated aPS contributed to efficient generation of reactive oxygen species including singlet oxygen and superoxide ion through both type 1 and type 2 pathways, alleviating the aerobic requirement for PDT. Equipped with a triphenylphosphine ligand for mitochondria targeting, mito aPS showed excellent phototoxicity to tumor cells with low light fluence under both normoxic and hypoxic conditions, after activation by intracellular GSH and H2 O2 . The mito aPS was also compatible to near infrared PDT with two photon excitation (800 nm) for extensive bioapplications. Abstract : Activatable photosensitizers (aPSs) possessing a benzothiadiazole fluorophore are designed for glutathione and hydrogen peroxide mutually responsive photodynamic therapy (PDT). Dual type 1 and type 2 photosensitizing pathway is available to generate multiple reactive oxygen species and counteract hypoxic environments. The mitochondria targeted aPS showed prominent antitumor effect by near infrared two‐photon PDT.